Redescription of Bactronophorus thoracites Gould (1856) and Bankia gracilis Moll (1935) from Sabah Waters, Malaysia, with Short Ecological Notes and Measurements Metrics - Loo Zhen Ann; Chen Cheng Ann; Khairul Adha Abd Rahim; Farah Diba (Jurnal Ilmiah Perikanan dan Kelautan, 2022)
Highlight ResearchRedescription of marine woodborers, Bactronophorus thoracites and Bankia gracilis from the region were illustrated.New records of Bactronophorus thoracites and Bankia gracilis from the region.Addition info on the measurements of pallets was recorded.Certain ecological data on the habitat of marine woodborers Bactronophorus thoracites and Bankia gracilis were documented.AbstractMollusc wood-borers are classified into two groups: pholads and teredinids. While pholads have a limited distribution to temperate and tropical marine waters, teredinids are found worldwide. However, limited info on the taxonomy was documented on the marine wood borer in Sabah, Malaysia. Present study focuses on determining the wood borer species from Sabah waters, Malaysia. Samples were collected from fallen tree debris in the mangrove at Kota Kinabalu, Kuala Penyu and W.P. Labuan during low tide and water quality parameters were taken in-situ from all three sampling sites. Specimen identification was carried out by observing the physical characteristics of the pallets which are unique between genuses. The species Bactronophorus thoracites was identified from the Kota Kinabalu sampling site and species Bankia gracilis were found in both the Kuala Penyu and W.P. Labuan sampling site. The pallet of B. thoracite are of "dagger-and-sheath” shape, it is 26mm in length, with blade measuring 10mm in length, basal cup 4mm in length and stalk 12mm in length. The pallet of B.gracilis is characterized by the dark periostacum covering the 3-lobbed upper margin of the calcareous portion of the inner face of the cone, the pallet is 20mm in length, with the blade and stalk both measuring 10mm in length. The present study described two species of marine wood borers namely B. thoracites and B. gracilis in Sabah and W.P. Labuan with some measurement metrics and ecological parameters that were missing from previous studies that aided the process of species identification in future.